H∞ Anti-Disturbance Bumpless Transfer Control for Switched Affine Systems With Its Application to a Circuit Model - Xie, Jing; Su, Han; Yang, Dong; Niu, Ben (IEEE transactions on circuits and systems. II, Express briefs, 2025)
This brief concentrates on the problem of H_{∞ } anti-disturbance bumpless transfer control (ADBTC) of switched affine systems (SASs) with multiple types of disturbances. The H_{∞ } ADBTC strategy is put forward to achieve the bumpless transfer (BT) performance and the anti-disturbance performance, simultaneously. First, a more general switched affine disturbance observer is designed to estimate the external disturbances generated from the external SASs. Secondly, a novel BT performance constraint containing the system state, the disturbance observer state, and the affine terms is proposed to suppress the control bumps. Thirdly, a switched anti-disturbance BT controller and a state-dependent switching law are constructed. Then a solvable condition for the H_{∞ } ADBTC problem of SASs is derived. Finally, the proposed control scheme is validated by an example of a circuit model.